2021
DOI: 10.1186/s12912-021-00644-w
|View full text |Cite
|
Sign up to set email alerts
|

Fear of future workplace violence and its influencing factors among nurses in Shandong, China: a cross-sectional study

Abstract: Background Fear of workplace violence has become a critical issue worldwide, which can lead to burnout, low levels of job satisfaction, and turnover. However, to date, little attention has been directed toward fear of workplace violence among nurses. Accordingly, this study investigated the level of fear of future workplace violence and its influencing factors among nurses in Shandong, China. Methods A cross-sectional study was conducted from July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…For MHPs, we found that lower income levels and managers were at higher risk of WPV. These two factors were also supported to be associated with WPV among different kinds of HPs ( 51 , 52 ). As we know, in Chinese families and traditional culture, men should take more responsibility in their families than women, and this makes them may care about their income.…”
Section: Discussionmentioning
confidence: 73%
“…For MHPs, we found that lower income levels and managers were at higher risk of WPV. These two factors were also supported to be associated with WPV among different kinds of HPs ( 51 , 52 ). As we know, in Chinese families and traditional culture, men should take more responsibility in their families than women, and this makes them may care about their income.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, the results are consistent with a previous study conducted in China that female nurses were more likely to have high levels of fear than male nurses (Huang et al, 2020 ). Meanwhile, previous reports showed that nurses who were married and with children had higher levels of fear than single, widowed, and separated nurses (Fu et al, 2021 ). A possible reason for this fear among married nurses was the fear of carrying the virus from their work and transferring it to their families.…”
Section: Discussionmentioning
confidence: 99%
“…. Working time was categorized according to a previous study ( 27 ) . c Monthly income was categorized according to a previous study ( 29 ) .…”
Section: Resultsmentioning
confidence: 99%
“…This research was conducted using the Wenjuanxing tool, which is a commonly used online survey tool in China. Through WeChat (a common social media app), we sent mobile users a web page with the questionnaire ( 27 ). Each computer or phone account should just submit one answer.…”
Section: Methodsmentioning
confidence: 99%